PERBANDINGAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII YANG DIAJAR DENGAN MENGGUNAKAN MEDIA INTERAKTIF DAN YANG DIAJAR MENGGUNAKAN MEDIA GAMBAR DI SMP N 2 PAINAN KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Fitri, Miarda; Mulyati, Mulyati; Yasmi, Fifi (Pendidikan Biologi, 2013)
ABSTRACT  Learning result in   junior high school biology 2 Painan still below the minimum completeness criteria (KKM). Lack of student learning result is caused by several things, such as lack adequately supported by a conducive classroom situation, so students tend to be noisy and play around when the teacher presents the lesson and less varied media used by teachers in the learning process. This study aimed to comparison the results of biological studies VIII grade students on the material growth and development are taught using interactive media and is taught using picture media. This type of research is experimental, the research design used in this study is the Only Randomized Control Group Posttest Design. This study was conducted in July-August 2013. The population is all students in grade VIII junior high school 2 Painan listed in the school year 2013/2014. Sampling with purposive sampling technique and  obtained VIII3   class as  a class experiment 1 were taught using interactive media and VIII5 class as a class experimental 2 taught by using picture media. The instrument used is in the form of a written test objective. Based on the achievement test scores of biology students, earned an average grade experiment 1 was 75,68 and the average class experiment 2 was 61,95. Data were analyzed using t-test. Of the t-test analysis, obtained t (5,89) > t table (1,68) which means that H1 is accepted. Thus it can be concluded that there are biological differences in learning result of students on the material growth and development by using interactive media and picture media of class VIII Semester 1 Junior High School N 2 Painan Kecamatan IV Jurai Kabupaten Pesisir Selatan.